Experimental study of the particle agglomeration on its mechanical properties of collapsible loess - Meng Zhao; Meng Zhao; Hong-Gang Wu; Wei Guo; Bo-Ren Tan; Cheng Hu; Rui Deng; Li-Yi Chen (Frontiers in Earth Science, 2022)
Loess, distributed all over the world, exhibits the behavior that is related to their formation history, mineralogy, and microstructure, which can cause serious geotechnical engineering problems. This paper presents the Baozhong railway is a key transportation channel for Guyuan city in Ningxia province of northwestern China. Based on field investigations treasure middle section of the railway in the study area, it is found that the more serious diseases subgrade settlement, local roads embankment platform dislocation occurs and lots of cracks were founded. For several years, with the train speed increasing, and due to the influence of widespread flood irrigation on the farmland, the subgrade experienced a degree of settlement. This settlement was not alleviated after three treatments, which seriously affected train safety. In order to analyze the reason for the railway line settlement, soil samples were collected from the collapsible loess subgrade. Consolidation test, particle size analysis test, X-ray diffraction test (XRD), and scanning electron microscopy test (SEM) were performed to investigate the mechanism of the subgrade disease. The results reveal that loess collected from severe differential settlements at locations has a highly compressible, and its clay content and agglomeration level was generally low. These results illustrated that the particle size of 20–50 microns has a direct effect on its mechanical properties of loess. This part of the particles has a cementation effect. It can effectively connect the large particles of the skeleton to form particle agglomerates and is an effective composition of loess clay minerals. Therefore, the loess structure was not stable due to its relatively low internal molecular attraction. When such saturated collapsible loess subgrade subjected to train vibration load, the soil might be liquefied, and its structure might be instable. If the drainage of the subgrade was not well designed, severe differential settlements would occur. The research is of great significance to clarify the relationship between loess particle composition, microstructure and its macromechanics, providing a vital reference for the engineering construction in the loess-dominated areas.